Using BASIC. - Didday, Richard L. (West Publishing Co., 1981)
"The central of Using BASIC is practicality. This book presents • A practical, systematic approach to program design. • Pragmatic, useful programs solving problems met by practicing programmers time anda again. • Programs which interact with the user in a helpful, polite way, saving the user time and frustation. • Portable programs which may be run on a variety of BASIC systems with minimal changes." (Copied from the preface).